Gastroprotective activity of a novel Schiff base derived dibromo substituted compound against ethanol-induced acute gastric lesions in rats - Saremi, Kamelia; Rad, Sima Kianpour; Tayeby, Faezeh; Abdulla, Mahmood Ameen; Karimian, Hamed; Majid, Nazia Abdul (BMC, 2019)
Background: Basic function of bromine in body is to activate pepsin production in gastritis with low acidity. The present study encompasses a broad in vivo study to evaluate gastroprotective activity of a novel dibromo substituted Schiff base complex against Sprague Dawley (SD) rats. Methods: 2, 2-[1, 2-cyclohexanediylbis (nitriloethylidyne)]bis(4-bromophenol) (CNBP) is synthesized via a Schiff base reaction, using the related ketone and diamine as the starting materials. SD rats are divided as normal, ulcer control (5 ml/kg of 10% Tween 20), testing (10 and 20 mg/kg of CNBP) and reference groups (omeprazole 20 mg/kg). Except for the normal group, the rest of the groups are induced gastric ulcer by ethanol 1 h after the pre-treatment. Ulcer area, gastric wall mucus, and acidity of gastric content of the animal stomachs are measured after euthanization. Antioxidant activity of the compound is tested by Ferric reducing antioxidant power (FRAP) test and safety of the compound is identified through acute toxicity by [3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. Moreover, activities of superoxide dismutase (SOD), catalase (CAT), levels of prostaglandins E2 (PGE2) and also malondialdehyde (MDA) are determined. Results: Antioxidant activity of CNBP was approved via FRAP assay. Vast shallow hemorrhagic injury of gastric glandular mucosa was observed in the ulcer group compared to the CNBP-treated animals. Histological evaluations confirmed stomach epithelial defense effect of CNBP with drastic decrease of gastric ulceration, edema and leucocytes penetration of submucosal stratum. Immunostaining exhibited over-expression in HSP70 protein in CNBP-treated groups compared to that of the ulcer group. Also, gastric protein analysis showed low levels of MDA, PGE2 and high activity of SOD and CAT. Conclusions: CNBP with noticeable antioxidant property showed gastroprotective activity in the testing rodents via alteration of HSP70 protein expression. Also, antioxidant enzyme activities which were changed after treatment with CNBP in the animals could be elucidated as its gastroprotective properties. © The Author(s). 2019.